Analysis of the Hadith on the Benefits of Honey, Olive Oil, and Black Cumin Seeds and Their Impact on Men's Reproductive Health - Fauzan Akbar; Munandar Munandar; Muhammad Nuh Siregar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze hadiths that mention the benefits of honey, olive oil, and black cumin seeds and evaluate their impact on men's reproductive health. Men's reproductive health is a major focus in the health sector, particularly in the context of disease prevention and maintaining sexual function. The research method used is a literature study with a textual analysis approach to the hadiths that discuss this topic, as well as reviewing scientific research related to the effects of honey, olive oil, and black cumin seeds on men's reproductive health. The results show that honey, olive oil, and black cumin seeds have therapeutic properties that can support men's sexual and reproductive health, such as improving sperm quality, increasing libido, and overcoming impotence problems. In conclusion, the use of honey, olive oil, and black cumin seeds according to the recommendations in the hadith can have a positive impact on men's reproductive health, with the note that further research is needed to explore their biological mechanisms.